Concentric isokinetic training and hypertrophy of the quadriceps femoris muscle - Housh, D. J.; Housh, T. J.; Weir, J. P.; Weir, L. L.; Donlin, P. E.; Chu, W. K (Medicine & Science in Sports & Exercise, 1996)
Concentric isokinetic training on the thigh of one leg produced increased strength and hypertrophy as well as a transfer effect of strength gain in the untrained limb which was not accompanied by hypertrophy. Implication: In cases of particular injuries, it could be possible to train for strength on the uninjured limb and maintain some stimulation for a trained state in the inactive injured limb.